Emission Characteristics of Heat Recirculating Porous Burners With High Temperature Energy Extraction - Banerjee, Abhisek; Saveliev, Alexei (Frontiers in Chemistry, 2020)
Emission characteristics of heat recirculating porous burners with high temperature heat extraction are studied numerically. Two types of burners are considered: counterflow porous burner (CFB) and reciprocal counterflow porous burner (RCFB). The combustion of methane-air mixtures flowing through the porous media is modeled by solving steady state governing equations to obtain the flame temperature and species profiles. Formation of CO, NO, NO2 and NOx is studied in CFB and RCFB in a range of equivalence ratios from 0.3 to 1.0 and heat extraction temperatures from 300 K to 1300 K. The contribution of various NO formation mechanisms is comparatively analyzed and related to the NO generation predicted by a detailed chemistry mechanism. The effect of high temperature heat extraction on the formation of CO and NOx is analyzed. Numerical predictions indicate a constant monotonic decrease of NOx concentration with increasing temperature of energy extraction. The formation of CO is observed to follow the similar trend. For heat extraction at 1300 K, simulations predicted 3.6 ppm of NOx and 3.9 ppm of CO for CFB and 4.1 ppm of NOx and 3.5 ppm of CO for RCFB when these burners are operated at an equivalence ratio of 0.7.